Great Powers' Struggle: Is the World Heading Toward Bipolarity Again? - Harun Semercioğlu (İmgelem)
After the 2020 pandemic, there has been an increasing academic discourse describing the emergence of a new bipolar international system centered around the United States (US) and the People's Republic of China (PRC). This article aims to test the hypothesis that “the struggle between these superpowers, as seen in the reshaped global order following the 2020 pandemic, will once again bring about a ‘bipolar world order’ similar to that of the Cold War.” In this context, the conceptual framework of the bipolar world order will be outlined, followed by an analysis of the national power elements of the two countries within the framework of realist theory. The international implications of their competition will then be analyzed in the conclusion. A quantitative research method will be employed to collect the necessary data, which will be analyzed using content analysis techniques. Finally, the accuracy of the tested hypothesis will be discussed and evaluated.